Crop Choice and Infrastructure Accessibility in Tanzania : Subsistence Crops or Export Crops? - Iimi, Atsushi; Humphreys, Richard Martin; Melibaeva, Sevara (World Bank, Washington, DC, 2015)
Africa has great potential for agriculture. Although international commodity prices have been buoyant, Africa’s supply response seems to be weak. A variety of constraints may exist. Using the case of Tanzania, the paper examines the impact of market connectivity, domestic and international, on farmers’ crop choices. It is shown that the international market connectivity, measured by transport costs to the maritime port, is important for farmers to choose export crops, such as cotton and tobacco. Internal connectivity to the domestic market is also found to be important for growing food crops, such as maize and rice. Among other inputs, access to irrigation and improved seed availability are also important factors in the crop choices of farmers. The size of land area is one constraint to promote the crop shift. The paper also reports the finding that farmers are not using market prices effectively in their choice of crop, even after the endogeneity of local prices is taken into account.